Mali : 2008 Article IV Consultation and Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility; Staff Report; Staff Supplements; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Mali. (IMF Staff Country Reports; Country Report ;, 2008)
Mali's 2008 Article IV Consultation and request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility are discussed. Mali's economy has doubled in size since the democratic transition of the early 1990s. Sound macroeconomic management has produced growth averaging almost 5 percent, and raised the tax ratio from less than 10 percent of GDP to about 16 percent. Agriculture, the mainstay of the economy, has been buffeted by recurrent droughts, floods, locust infestation, and diseases.